Banana stem and chicken eggshells as a filler of polyester composites for particleboard application - Okta Bani; Abhishek Agarwal; Richard; Heinrich (Discover Materials)
Abstract This study investigates banana stem powder (BSP) and nano-enhanced CaO powder (NCP) from chicken eggshells as sustainable fillers in polyester composites, evaluating their potential as particleboard alternatives against Indonesian Standard SNI 03–2105–2006. Composites (80% resin, 20% filler; BSP/NCP ratios: 5:15–15:5) were compression-moulded at 90 °C for 15–25 min, with no-filler controls prepared for each moulding time. Due to resource constraints, each formulation was tested once. Results demonstrated that optimized composites (15% NCP, 5% BSP, 25 min) achieved a 1927% increase in MOR (325 MPa vs. control), 0.9% moisture absorption, and 2% thickness swelling, meeting SNI thresholds for these properties—though density exceeded requirements. FTIR spectroscopy indicated non-chemical interactions, while SEM revealed filler agglomeration. Despite these limitations, the composite’s exceptional mechanical and hygroscopic performance supports its use in applications where density is secondary to strength. Future work should include statistical validation and assess additional properties (e.g., MOE, emissions). Graphical Abstract